PEMANFAATAN POTENSI SUMBER DAYA MANUSIA DI LINGKUNGAN SEKOLAH SEBAGAI DASAR PENGEMBANGAN DESA - Syamsu Nurkarim; Chandra Gunawan (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Sukaraharja Village has an interest in the role of Human Resources development for the progress of its own village, this is proven by the community's huge interest in community service activities, Karang Taruna, Community Groups, LPMK and also Village Apparatus and Bumdes participate in its implementation. Based on the various kinds of community activities carried out by Sukaraharja Village, there are social sources interested in the development, especially the economy of the community, which come from Village funds, but this has not been supported by strong management of the utilization of human resources in the surrounding area, this is proven with the potential for businesses that are not yet on target because they relate to human resources. There needs to be socialization, planning, guidance, implementation and monitoring of activities, especially the development of unique micro businesses managed by the Village, by utilizing human resources who have strong skills for the development of Sukaraharja Village